On Capital Structure Arbitrage : Analyzing the Effects of Structural Credit Risk Model Calibration and Equity Variance Hedging - Mäkilä, Valtteri (My University, 2020)
After the turn of the millennium, a strategy called capital structure arbitrage started to gain interest among academics and practitioners. In this relative value trading strategy, a structural credit risk model is used to identify dislocations in the pricing of a firm’s capital structure. If a pricing misalignment between a company’s debt and equity instruments is found, a balanced relative value position including both debt and equity instruments is established. In a scenario where the prices converge back to their fundamental values, the trade should be profitable. In this thesis, both the structural credit risk model used to generate the trading signals and the strategy execution in itself are analyzed. First, the aim is to test how the Merton (1974) Moody’s KMV credit risk model performs in a capital structure arbitrage setting when different calibration methodologies are utilized. Second, a new trading execution strategy involving variance and credit default swaps is tested. To test the model and the proposed strategy execution methodology, a sample consisting of 102 European obligors is analyzed during the post-financial crisis era spanning from 2.8.2012 to 30.7.2019. Finally, results are compared to previous studies so that conclusions regarding the viability of the tested approach can be made. The results indicate that the use of market-implied data, e.g., implied equity volatility, in the model calibration leads to improved model accuracy and higher trading strategy profits on average. Similar results are found if Student’s t-distribution is applied in default probability calculations instead of the normal distribution. Additionally, the use of variance swaps in the trading strategy can be seen as a valid alternative compared to cash equities, for example. With the best-performing model variant, Sharpe ratios calculated from monthly excess returns vary between 0.43 and 0.59. Altogether, both the Merton (1974) Moody’s KMV and the variance swap-based execution strategy can be seen to perform inline or in some instances even better than other model and strategy specifications when the results are compared to previous studies.

Vuosituhannen vaihteessa akateemikot ja edistykselliset sijoittajat alkoivat kiinnittää entistä enemmän huomiota uuteen strategiaan, joka nojautui yksittäisen yhtiön pääomarakenteessa ilmenevien hinnoitteluvirheiden hyödyntämiseen. Tässä pääomarakennearbitraasiksikin kutsutussa strategiassa sijoitetaan riskiekvivalentisti yhtiön osakkeesta ja luottoriskistä riippuvaisiin instrumentteihin, mikäli hinnoitteluvirhe onnistutaan havaitsemaan rakenteellista luottoriskimallia hyödyntämällä. Olettaen, että käytetty luottoriskimalli tuottaa luotettavia signaaleja pitäisi hankittujen instrumenttien nettotuoton olla positiivinen, kun hinnoitteluvirhe markkinoilla korjautuu. Tässä tutkielmassa tarkastellaan sekä signaaleja tuottavaa rakenteellista luottoriskimallia että strategian toteuttamista käytännössä. Tutkimusongelma rakentuu kahden osa-alueen varaan. Ensinnäkin tavoitteena on testata millaisia tuloksia Merton (1974) Moody’s KMV -luottoriskimallilla ja sen erilaisilla kalibraatiometodeilla on mahdollista saavuttaa pääomarakennearbitraasiin keskittyvässä viitekehyksessä. Tämän lisäksi analysoidaan uutta strategian toteutusmetodia, jossa hyödynnetään varianssin (varianssiswap) ja luottoriskin vaihtosopimuksia. Tulokset lasketaan otoksesta, joka koostuu 102 eurooppalaisesta yrityksestä ja joka ulottuu elokuusta 2011 aina heinäkuuhun 2019 saakka. Jotta lähestymistavan tehokkuutta voidaan kommentoida, vertaillaan tuloksia aikaisemmissa tutkimuksissa käsiteltyihin tuloksiin. Tulokset osoittavat, että markkinoilta johdetun informaation ja Studentin t-jakauman käyttö normaalijakauman sijaan luottoriskimarginaaleja laskettaessa johtavat keskimäärin korkeampiin strategiatuottoihin ja parantuneeseen ennustetarkkuuteen. Lisäksi huomataan, että varianssin vaihtosopimukset toimivat strategiaa toteutettaessa osakkeita vastaavalla tavalla. Soveltuvimman strategiavariantin kuukausittaisista ylituotoista laskettu Sharpen luku kustannusten jälkeen on 0,43 ja 0,59 välillä riippuen strategian toteutustavasta. Tulosten valossa voi siis todeta, että Merton (1974) Moody’s KMV -malliin nojaavilla luottoriskiennusteilla ja varianssin vaihtosopimuksiin pohjaavalla strategialla voidaan saavuttaa tuloksia, jotka ovat linjassa aikaisempien tutkimustulosten kanssa kanssa.
Keywords: Capital structure arbitrage, Merton model, Moody’s KMV, variance swap, CDS